Analisis Pemasaran Ikan Konsumsi Keramba Jaring Apung Waduk Jatiluhur Zona 1, Kecamatan Purwakarta, Kabupaten Purwakarta - Fajrin Audy Husnandina; Atikah Nurhayati; Asep Agus Handaka Suryana; Ine Maulina (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
Purwakarta Regency has aquaculture production reaching 94.5 thousand tons only from KJA cultivation, making it the area with the highest aquaculture production in West Java. One that has high potential to produce abundant fish cultivation production is the Jatiluhur Reservoir. However, the abundant production of food fish cultivation in the Jatiluhur Reservoir will suffer losses if it is not accompanied by a fast and precise marketing process. This research was carried out in Jatiluhur Reservoir zone 1, Purwakarta District, Purwakarta Regency with research time from October 2023 to February 2024. The aim of this research is to analyze curiosity channel patterns, marketing costs, profits, margins, farmer's share, benefit cost ratio and marketing efficiency of consumption fish cultivated using the KJA cultivation system in Jatiluhur Reservoir zone 1. Sampling in this research used purposive sampling and snowball sampling methods, meanwhile data was analyzed using qualitative and quantitative descriptive methods. The results of this research are that the marketing channels for consumption fish are divided into three with marketing channel III being the most efficient, marketing for carp is more efficient than tilapia and the marketing business for consumption fish can be said to be feasible because it has an average BCR value of >1.